Analisis Kemampuan Literasi Numerasi Pada Siswa Kelas IV Di SD Negeri Tlogosari 01 Semarang - Anita Dian Pratiwi; Aryo Andri Nugroho; Rina Dwi Setyawati; Susilo Raharjo (Universitas Ngudi Waluyo, 2023)
The culture of literacy in Indonesia is so low, the factor that affects the low literacy in Indonesia is the lack of interest in reading in Indonesian society. Literacy itself can be related to skills in certain fields. Literacy that is closely related to the ability to think critically is numeracy literacy. Numeracy literacy is closely related to mathematics so that numeracy literacy is the ability to reason using language and mathematics. This research uses descriptive qualitative research. The purpose of this research is to analyze the numeracy literacy skills of grade IV students. The subject of this research involved 6 fourth grade students at SDN Tlogosari Kulon 01 Semarang. The research instruments used were interviews and worksheets in the form of student math story problems to analyze students' numeracy literacy skills. Based on the results of research from 6 students who worked on worksheets in the form of math story problems, there was one student who had low-level numeracy literacy skills, 3 people had medium-level numeracy literacy skills, and 2 students had high-level numeracy literacy skills. So it can be concluded that the numeracy literacy skills of fourth grade students at SDN Tlogosari Kulon 01 Semarang are at a moderate level. Budaya literasi di Indonesia termasuk rendah, faktor yang mempengaruhi rendahnya literasi di Indonesia adalah kurang minat baca pada masyarakat Indonesia. Literasi sendiri dapat dihubungkan dengan keterampilan di bidang terntu. Literasi yang berkaitan erat dengan kemampuan dalam berpikir kritis adalah literasi numerasi. Literasi numerasi berkaitan erat dengan matematika sehingga literasi numerasi adalah kemampuan bernalar menggunakan bahasa dan matematika. Penelitian ini menggunakan penelitian kualitatif jenis deskriptif. Tujuan penelitian dilakukan penelitian ini adalah untuk menganalisis kemampuan literasi numerasi siswa kelas IV. Subjek penelitian ini melibatkan 6 siswa kelas IV di SDN Tlogosari Kulon 01 Semarang. Instrumen penelitian yang digunakan adalah wawancara dan hasil lembar kerja berupa soal cerita matematika siswa untuk menganalisis kemampuan literasi numerasi siswa. Berdasarkan hasil penelitian dari 6 siswa yang mengerjakan lembar kerja berupa soal cerita matematika terdapat satu siswa memiliki kemampuan literasi numerasi tingkat rendah, 3 orang memiliki kemampuan literasi numerasi tingkat sedang, dan 2 siswa memiliki kemampuan literasi numerasi tingkat tinggi. Sehingga dapat simpulkan bahwa kemampuan literasi numerasi siswa kelas IV di SDN Tlogosari Kulon 01 Semarang berada ditingkat sedang.